2011
DOI: 10.4111/kju.2011.52.8.507
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Benign Prostatic Hyperplasia: Evidence of a Potential Relationship, Hypothesized Etiology, and Prevention

Abstract: Benign prostatic hyperplasia (BPH) is highly prevalent in older men and causes substantial adverse effects on health. The pathogenesis of this disease is not totally clear. Recent reports have suggested a possible relationship between metabolic syndrome (MetS) and BPH. Single components of MetS (obesity, dyslipidemia, hypertension, and insulin resistance) as well as the syndrome itself may predispose patients to a higher risk of BPH and lower urinary tract symptoms (LUTS). This may stem from changes in insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 85 publications
(110 reference statements)
2
38
0
2
Order By: Relevance
“…The enhancement of the RhoA/ROCK contractile signaling in bladder smooth muscle is regarded as one of the main molecular mechanisms underlying bladder overactivity and storage LUTS. It has been described that RhoA/ROCK pathway is enhanced in several pathological conditions, including MetS [2,31,45,46]. In the present study we found that MetS bladder preparations show an increased RhoA membrane docking (2.5-fold) and an increased expression of RhoA-dependent genes, such as ROCK1, alpha-SMA and desmin.…”
Section: Discussionmentioning
confidence: 43%
“…The enhancement of the RhoA/ROCK contractile signaling in bladder smooth muscle is regarded as one of the main molecular mechanisms underlying bladder overactivity and storage LUTS. It has been described that RhoA/ROCK pathway is enhanced in several pathological conditions, including MetS [2,31,45,46]. In the present study we found that MetS bladder preparations show an increased RhoA membrane docking (2.5-fold) and an increased expression of RhoA-dependent genes, such as ROCK1, alpha-SMA and desmin.…”
Section: Discussionmentioning
confidence: 43%
“…Changes in sex hormones may also play a role in the association between BPH and metabolic syndrome. A combination of low testosterone and high oestradiol levels may increase the risk of BPH, and this combination of hormone levels is also found in men with metabolic syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Embora os fatores de risco não modificáveis, como idade, genética e geografia, desempenhem papéis importantes na etiologia da HBP, dados recentes revelaram que fatores de risco modificáveis estão associados com a prevenção da doença e alívio dos sintomas, incluindo obesidade, diabetes, dieta, atividade física e inflamação (18) . Estudos publicados na Coreia do Sul sugeriram que a perda de peso e a atividade física regular poderiam ser úteis para o alívio sintomático da HPB (19,20) . A significativa diferença na expectativa de vida entre homens e mulheres sugere que os primeiros são um grupo mais vulnerável, necessitando de programas de promoção da saúde direcionados, que atuem nos fatores de risco modificáveis, a fim de envolver o homem com a sua saúde ou gestão de doença (21) .…”
Section: Discussionunclassified